The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/acr.25072
|View full text |Cite
|
Sign up to set email alerts
|

Association of Traumatic Knee Injury With Radiographic Evidence of Knee Osteoarthritis in Military Officers

Abstract: Objective The association between knee injury and knee osteoarthritis (OA) is understudied relative to its importance, particularly in younger populations. This study was undertaken to examine the association of knee injury with radiographic features of knee OA in military officers, who have a physically demanding profession and high rates of knee injury. Methods Participants were recruited in 2015–2017 from an existing program that enrolled 6,452 military officers during 2004–2009. Officers with a history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Trauma resulting from sports participation has been linked with the subsequent development of OA [ 32 , 33 ], which may be an underlying risk factor in this cohort. Currently, medical interventions are mostly symptomatic, and are inadequate to prevent the development of OA, or to dramatically improve pre-existing OA.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma resulting from sports participation has been linked with the subsequent development of OA [ 32 , 33 ], which may be an underlying risk factor in this cohort. Currently, medical interventions are mostly symptomatic, and are inadequate to prevent the development of OA, or to dramatically improve pre-existing OA.…”
Section: Discussionmentioning
confidence: 99%
“…The current key research priorities are to understand pathophysiological mechanisms, earlier recognition and diagnosis, and optimalisation of prevention and management strategies (particularly relevant for PTOA, as the index trauma should initiate preventative interventions). [7,[10][11]25] A particular challenge in the research, and clinical, fields relate to the significant discordance between imaging (radiographic or structural OA), knee pain (symptomatic OA), and a physiciandiagnosed OA, a result of the poorly understood interactions between risk and individual factors (Figure 1). A recent US military study showed less than half of those with radiological OA reported symptoms.…”
Section: Directions Of Further Researchmentioning
confidence: 99%
“…A recent US military study showed less than half of those with radiological OA reported symptoms. [10] Another way to frame this discordance is to describe either the OA disease (underlying pathophysiology and cellular biology) or the OA illness (an individual's feeling or experience, characterised by symptoms, function and quality of life). [11] Regardless of terminology used, this phenomenon has implications for the design of clinical research studies, understanding pathways and markers associated with disability, dysfunction and pain, as well as future OA diagnostic criteria.…”
Section: Directions Of Further Researchmentioning
confidence: 99%
See 2 more Smart Citations